The Neural Substrate of Sex Pheromone Signalling in Male Goldfish (Carassius auratus) - Lado, Wudu E. (Université d'Ottawa / University of Ottawa, 2012)
The transmission of sex pheromone-mediated signals is essential for goldfish reproduction. However, the neural pathways underlying this reproductive signalling pathway in the goldfish brain is not well described. Lesioning experiments have shown previously that two brain areas, the preoptic area (POA) and the ventral telencephali pars ventralis (Vv) in particular, are important for reproduction. We used patch clamp electrophysiology to study the electrical activities of POA and Vv neurons. Based on the intrinsic properties of these neurons, we suggest there are five different functional classes of POA neurons and a single class of Vv neurons. In addition, by electrically stimulating the olfactory bulb (OB), we were able to show that this primary sensory structure makes monosynaptic glutamatergic connections with both POA and Vv neurons. While electrophysiology measures signalling events occurring at short time scales on the order of milliseconds to minutes, we were also interested in studying sex pheromone signalling in the goldfish brain over a long time scale. Thus, we describe changes in gene expression in male goldfish exposed to waterborne sex pheromones (17alpha,20beta dihydroxy-4-pregene-3-one and Prostaglandin-F2alpha) over 6 hours. We perform cDNA microarrays on Prostaglandin-F2alpha-treated fish to study the rapid modulation of transcription and define the signalling pathways affected. Our microarrays showed that 71 genes were differentially regulated (67 up and 4 down). Through gene ontology enrichment analysis, we found that these genes were involved in various biological processes such as RNA processing, neurotransmission, neuronal development, apoptosis, cellular metabolism and sexual reproduction. RT-PCRs were performed to validate our microarrays and to facilitate direct comparisons of the effects of the two sex pheromones, 17alpha,20beta dihydroxy-4-pregene-3-one and Prostaglandin-F2alpha. By combining electrophysiology and gene expression analyses, we were able to study sex-pheromone signalling on two different time scales. One short, occurring on the order of milliseconds to minutes, that involves electrical activities in the brain through the glutamatergic amino-3-hydroxy-5-methylisoxazole-4-propionate and N-methyl-D-aspartate receptors; and the other long occurring several hours later that involves changes in the gene expression levels of calmodulin and ependymin among other genes underlying neuroplasticity. Reproductive neuroplasticity in the goldfish may therefore require the activation of glutamatergic receptors which then activate downstream signals like calmodulin and ependymin to transform the sex pheromones-mediate signal into gene expression.
Keywords: Goldfish, reproduction, male, preoptic area, ventral telencephalon, sex pheromones; NMDAR, AMPAR, NMDA, AMAPA, glutamate; ventral telencephali pars ventralis, septal region; Prostaglandin F 2alpha, 17 alpha,20 beta-dihydroxy-4-pregnen-3-one; spawning, microarray analysis, patch-clamp electrophysiology; goldfish